2005
DOI: 10.1111/j.1365-2362.2005.01532.x
|View full text |Cite
|
Sign up to set email alerts
|

The epidemiology and control of anaemia among pre‐ESRD patients with chronic kidney disease

Abstract: Anaemia is a common condition among pre-end-stage renal disease (pre-ESRD) patients with chronic kidney disease (CKD). Indeed, data from clinical studies indicate that anaemia may be present in as many as two-thirds of such patients. Use of recombinant human erythropoietin (EPO) provides an effective means of correcting anaemia in CKD patients and helps to reduce the risk of renal disease progression and related problems. Unfortunately, EPO therapy is underutilized in these persons. Consequently, anaemia remai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 56 publications
(52 reference statements)
0
22
0
Order By: Relevance
“…Development of anemia in these patients often compromises lifestyle and may increase risk for mortality (2)(3)(4). A major factor contributing to the anemia consists of lineagespecific suppression of bone marrow erythropoiesis (5).…”
Section: Introductionmentioning
confidence: 99%
“…Development of anemia in these patients often compromises lifestyle and may increase risk for mortality (2)(3)(4). A major factor contributing to the anemia consists of lineagespecific suppression of bone marrow erythropoiesis (5).…”
Section: Introductionmentioning
confidence: 99%
“…This finding raises doubts about the reporting and integrity of other data elements on Form 2728, including the use of erythropoiesis-stimulating agents (ESAs) in patients before attaining ESRD and starting renal replacement therapy (predialysis period). ESAs are recommended and used to correct severe anemia, which occurs frequently as a complication of severe CKD, and may ameliorate many of the negative sequelae of anemia, which include lower quality of life and increased hospitalization, cardiovascular complications, and mortality [12][13][14][15][16][17][18][19][20]. Recent USRDS reports and clinical studies have suggested that ESA underuse in patients with pre-ESRD may be contributing to the unacceptable severity of anemia in these patients at initiation of dialysis [1][2][6][7][8][9][10]15,19].…”
Section: Introductionmentioning
confidence: 99%
“…ESAs are recommended and used to correct severe anemia, which occurs frequently as a complication of severe CKD, and may ameliorate many of the negative sequelae of anemia, which include lower quality of life and increased hospitalization, cardiovascular complications, and mortality [12][13][14][15][16][17][18][19][20]. Recent USRDS reports and clinical studies have suggested that ESA underuse in patients with pre-ESRD may be contributing to the unacceptable severity of anemia in these patients at initiation of dialysis [1][2][6][7][8][9][10]15,19]. To better understand the quality of the data underpinning these observations, we investigated the accuracy and completeness of predialysis ESA use data on Form 2728 by comparing them with Department of Veterans Affairs (VA) pharmacy prescription records and Medicare claims records in a cohort of veterans reliant on VA and/or Medicare-covered services.…”
Section: Introductionmentioning
confidence: 99%
“…However, most causes of ACDI are not curable, thus many patients with ACDI simply live with the symptoms and side effects. The adverse consequences of anemia in these patients range from activity-limiting fatigue to shortened life expectancy [8][9][10]. In treating these anemias, several nations spend billions of dollars per year on erythropoiesis stimulating agents (ESAs) [30,31], which consist of injectable recombinant human erythropoietin (Epo) and intravenous (IV) iron [32].…”
Section: Current Therapiesmentioning
confidence: 99%
“…Its adverse effects as well as an increased mortality rate [8][9][10] constitute a major public health problem.…”
Section: Clinical Definition/descriptionmentioning
confidence: 99%